Efficacy of antiviral therapy and host-virus interactions visualised using serial liver sampling with fine-needle aspirates - Kim, Samuel; Wallin, Jeffrey J.; Ghosheh, Yanal; Zahoor, Muhammad Atif; Sanchez Vasquez, Juan Diego; Nkongolo, Shirin; Fung, Scott; Mendez, Patricia; Feld, Jordan J.; Janssen, Harry L. A.; Gehring, Adam J. (JHEP reports, 2023)
Novel therapies for chronic hepatitis B (CHB), such as RNA interference, target all viral RNAs for degradation, whereas nucleoside analogues are thought to block reverse transcription with minimal impact on viral transcripts. However, limitations in technology and sampling frequency have been obstacles to measuring actual changes in HBV transcription in the liver of patients starting therapy.